(untitled) (Fiep Bulletin - online, 2013)
The "intercultural study of capoeira in Brazil (Rio de Janeiro) and French (Paris)" reveals us the sense that the practitioners of capoeira give to their physical practice in Brazil and French, as well the reunification of the social classes around of capoeira. As a type of quantitative survey, we applied the questionnaire on the views of practitioners with a total of 104 athletes of capoeira in Brazil and French. As an outcome of the study, the capoeira showed us that have not done a disruption linked to the cultural practices of physical activity in French yet, because is the social cultural values of Brazilian society that we see with capoeira in French. However, even if the rookies’ practitioners come to capoeira due to the relaxed atmosphere of practice, the most experienced still practice because of its internal logic. For countries studied, while in French the competitiveness in the game is a reflection of a society based on individualism that works each day to be more competitive, the Brazilian society evolving with their sport art, the pleasure of playing together, and with the swings and the malice of the capoeira, in life.